Case report: Wernicke–Korsakoff syndrome after bariatric surgery - Bento, Margarida Alves; Vieira, João Barriga; Silva, Maria Leonor; Camolas, José (Frontiers in Nutrition, 2024)
Vitamin and mineral deficiencies are prevalent nutritional disorders following bariatric surgery. Although they are more prevalent after malabsorptive procedures such as bypass, they also occur in restrictive procedures such as gastric sleeve. The mechanisms that lead to the occurrence of these deficits are related to the presence of poor nutritional intake or poor adherence to multivitamins and multimineral supplementation. Wernicke–Korsakoff syndrome (WKS) is an acute neurological disorder resulting from thiamine deficiency. This syndrome is composed of two distinct phases: first, Wernicke Encephalopathy (WE), the acute phase of this syndrome, which is characterized by a triad of mental confusion, ocular signs, and ataxia, followed by the chronic phase of WKS, called Korsakoff’s syndrome (KS), which is known for the presence of anterograde amnesia and confabulation. We aimed to report a case of a patient with WKS after bariatric surgery. The patient’s retrospective chart review was performed in order to retrieve the relevant clinical data. The patient was a 24-year-old female student with a BMI of 48 kg/m2 who underwent sleeve gastrectomy surgery for morbid obesity. Over the following 2 months, recovery from surgery was complicated by non-specific symptoms such as nausea, recurrent vomiting, and a significant reduction in food intake, which led the patient to visit the emergency department six times with hospitalization on the last occasion for a definitive diagnosis. During the 15 days of hospitalization, the patient developed ocular diplopia, nystagmus, complaints of rotatory vertigo, and gait abnormalities. A magnetic resonance imaging of the head was performed but revealed no significant changes. After a formal neurological assessment, treatment with parenteral thiamine (100 mg, three times a day) was started without prior dosing. The observed clinical improvement confirmed the diagnosis of WKS. Bariatric surgery may contribute to thiamine deficiency and, consequently, to WKS. Education about the adverse consequences of malnourishment is mandatory before and after the surgery. Investigation of nutritional deficiencies both pre- and post-operatively is crucial in order to prevent complications such as WKS.